Legal Aspects in Mergers and Acquisitions (M&A) in Indonesia - Indraswari, Sri Primawati; Yadav, Vishal; Rao, Ananya (Yayasan Pendidikan Islam Daarut Thufulah, 2025)
Background: Mergers and acquisitions (M&A) are integral to corporate strategies, playing a crucial role in business expansion and market consolidation. In Indonesia, the legal framework surrounding M&A is complex and influenced by various laws and regulations. The legal aspects of M&A transactions, including corporate governance, antitrust laws, and the protection of minority shareholders, are pivotal in ensuring that these corporate actions are legally sound and contribute to economic development. However, challenges such as regulatory ambiguities, incomplete legal integration, and inadequate enforcement mechanisms often hinder the smooth execution of M&A transactions. Objective: This study aims to analyze the legal aspects of mergers and acquisitions in Indonesia, focusing on the regulatory framework, legal procedures, and challenges faced by companies engaged in M&A. The research seeks to identify key legal considerations that impact the success and failure of M&A transactions in Indonesia, with a particular focus on corporate governance and antitrust regulations. Method: A qualitative research design was employed, utilizing legal document analysis, case studies, and interviews with legal professionals, corporate lawyers, and business executives. This approach allows for a comprehensive understanding of the legal landscape and practical challenges in M&A transactions. Results: The findings indicate that while Indonesia has a well-established legal framework for M&A, issues related to regulatory compliance, transparency, and legal enforcement remain significant obstacles. Conclusion: The study concludes that while the legal aspects of M&A in Indonesia are progressing, further improvements in regulatory clarity, enforcement, and corporate governance are needed to foster a more conducive environment for M&A transactions.